An Investigation of Foreign Language Teaching Anxiety among EFL and EMI Arab Teachers in UAE. - ALBIRBARY, RUBA (2023)
Teachers' fear, apprehension, unease, or worry might be related to foreign language teaching or teaching other subjects using foreign languages. This is referred to as "foreign language teaching anxiety". The present research aims at investigating teaching anxiety among EFL and EMI Arab teachers in UAE. The research questions are addressed using a transformational concurrent mixed method research. The study representative sample included one hundred thirty-six Arab EFL (English teachers) and EMI (math, science, and ICT teachers) from three different school types (American, British, and MOE curriculum schools) in the UAE. A mixed-form questionnaire was used as the research instrument. SPSS was used to analyze the study’s quantitative data. While qualitative data analysis was done through thematic analysis. According to the results, rarely do teachers experience foreign language teaching anxiety; they rarely faced problems of self-perception of language proficiency, teaching inexperience, fear of negative evaluation, and difficulties in time management. However, they sometimes faced a lack of students’ interest. The study indicates that there is a statistically significant difference in the level of foreign language teaching anxiety according to (gender, years of experience, school type, and age). The results of the study also showed that anxiety has positive impacts on teachers as it enhances their self-improvement, motivation, and creativity and it urges them to plan and self-control. On the other hand, teaching anxiety has negative impacts on teachers that affect their personality, teaching process, and evaluation. Future studies recommended may investigate other factors affecting teachers' anxiety. These factors include supervision and evaluation consequences, student level of language proficiency and type of the skill being taught.